Metabolome and microbiome profiling of a stress-sensitive rat model of gut-brain axis dysfunction - Bassett SA; Young W; Fraser K; Dalziel JE; Webster J; Ryan L; Fitzgerald P; Stanton C; Dinan TG; Cryan JF; Clarke G; Hyland N; et al. (Springer Nature Limited, 2019)
Stress negatively impacts gut and brain health. Individual differences in response to stress have been linked to genetic and environmental factors and more recently, a role for the gut microbiota in the regulation of stress-related changes has been demonstrated. However, the mechanisms by which these factors influence each other are poorly understood, and there are currently no established robust biomarkers of stress susceptibility. To determine the metabolic and microbial signatures underpinning physiological stress responses, we compared stress-sensitive Wistar Kyoto (WKY) rats to the normo-anxious Sprague Dawley (SD) strain. Here we report that acute stress-induced strain-specific changes in brain lipid metabolites were a prominent feature in WKY rats. The relative abundance of Lactococcus correlated with the relative proportions of many brain lipids. In contrast, plasma lipids were significantly elevated in response to stress in SD rats, but not in WKY rats. Supporting these findings, we found that the greatest difference between the SD and WKY microbiomes were the predicted relative abundance of microbial genes involved in lipid and energy metabolism. Our results provide potential insights for developing novel biomarkers of stress vulnerability, some of which appear genotype specific.
Keywords: Animals; Brain; Disease Models, Animal; Gastrointestinal Microbiome; Lactococcus; Lipid Metabolism; Lipids; Male; Metabolome; Rats; Rats, Inbred WKY; Rats, Sprague-Dawley; Stress, Physiological